Gly-Pro-Val-Gly-Pro-Ser Peptide Fish Collagen Improves Skin Moisture and Wrinkles with Ameliorated the Oxidative Stress and Pro-inflammatory Factors in Skin Photoaging Mimic Models - Cho, Wonhee; Park, Jeongjin; Lee, Minhee; Park, Seong-Hoo; Jung, Jaeeun; Kim, Jinhak; Eun, Sangwon; Kim, Jinkyung (Preventive nutrition and food science, 2023)
This study aimed to investigate whether low molecular fish collagen peptide (FC) from had protective effects on skin of photoaging mimic models. We observed that FC supplementation improved antioxidant enzymes activities and regulated the pro-inflammatory cytokines [e.g., tumor necrosis factor-α, interleukin (IL)-1β, and IL-6] by reducing the protein expressions of pro-inflammatory factors IκBα, p65, and cyclooxygenase-2 in ultraviolet-B (UV-B) irradiated and . Furthermore, FC increased hyaluronic acid, sphingomyelin, and skin hydration by reg-ulating the mRNA expression of hyaluronic acid synthases 1∼3, serine palmitoyltransferase 1, delta 4-desaturase, sphingolipid 1, and protein expressions of ceramide synthase 4, matrix metalloproteinase (MMP)-1, -2, and -9. In UV-B irradiated and , FC down-regulated the protein expression of the c-Jun N-terminal kinase, c-Fos, c-Jun, and MMP pathways and up-reg-ulated that of the transforming growth factor-β receptor I, collagen type I, procollagen type I, and small mothers against decapentaplegic homolog pathways. Our results suggest that FC can be effective against UV-B induced skin photoaging by improving skin dryness and wrinkle formation through antioxidant and anti-inflammatory properties.